"Asianness" under Construction: The Contours and Negotiation of Panethnic Identity/Culture among Interethnically Married Asian Americans. (February 2017) - Chong, Kelly H.
Based on life-history interviews of interethnically married U.S.-raised Asians, this article examines the meaning and dynamics of Asian American interethnic marriages, and what they reveal about the complex incorporative process of this "in-between" racial minority group into the U.S.. In particular, this article explores the connection between Asian American interethnic marriage and pan-Asian consciousness/identity, both in terms of how panethnicity shapes romantic/marital desires of individuals and how pan-Asian culture and identity is invented and negotiated in the process of family-making. My findings indicate that while strong pan-Asian consciousness/identity underlies the connection among intermarried couples, these unions are not simply a defensive effort to "preserve" Asian-ethnic identity and cultur against a society that still racializes Asian Americans, but a tentative and often unpremeditated effort to navigate a path toward integration into the society through an ethnically based, albeit hybrid and reconstructed identity and culture, that helps the respondents retain the integrity of "Asianness."